Gendered Impact of COVID-19 Pandemic on Transitioning from University to Labor Market: Evidence from Turkey - Merve Demirel-Derebasoglu; Cagla Okten (Institute of Labor Economics (IZA), 2022)
The Covid-19 pandemic led to unprecedented disruptions in the labor market. Turkey implemented a worker dismissal ban to mitigate the adverse effects, effective from April 2020 to June 2021. The pandemic and unveiled measures put pressure against recent university graduates' successful transition to the labor market, who are already vulnerable to labor market shocks due to a dramatic increase in their number in the last decade. In this paper, we examine the gendered impact of the Covid-19 pandemic and related employment protection policies on the labor market outcomes of recent university graduates. We find that both males and females are less likely to be employed during the pandemic year, with more pronounced employment losses for females. While gender differences in employment arise from females' high skill employment losses, becoming discouraged workers and staying out of the labor force to invest in self-education led to higher inactivity for females.
Keywords: I14; J21; J16; J08; 330; COVID-19; employment; gender; employment protection policies; Turkey